Trihexyphenidyl abuse in psychiatric outpatient clinic of a general hospital in Northern Nigeria - Raji Saheed Olanrewaju; Abba Mannir (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Background: Concomitant prescription of anticholinergics with first generation antipsychotic medications is widely practiced in psychiatry to avert or abort extrapyramidal side effect resulting from the latter. Trihexyphenidyl (Benzhexol) is the most commonly prescribed and the most likely to be abused amidst the anticholinergics in Nigeria.   Objectives: To explore the prevalence and the associated factors for Trihexyphenidyl abuse among psychiatric outpatients in Nigeria.  Methodology: 64 stable outpatients who met the inclusion criteria were interviewed with a sociodemographic questionnaire and a ten items Drug Abuse Screening Test (DAST-10), other relevant data were obtained from their case notes at the psychiatric clinic of Sarkin Maska Shehu (SMASH) Hospital, Funtua, Katsina State. Data were tabulated and analysed with Microsoft Excel and version 11.65 of Window Program for Epidemiologist (WINPEPI).  Result: Mean age of participants was 36years, 33 (51.60%) of the participants were males, 24 (37.50%) were married while 36 (56.25%) were employed. Schizophrenia (38, 59.40%) was the leading axis 1 diagnoses among the studied participants. 16 (25.%) of the participants met the criteria for Trihexyphenidyl abuse.  Conclusion and Recommendations: Abuse potential of the Benzhexol and other anticholinergics calls for caution in its prescription amidst other disadvantages. Choice of atypical antipsychotics, gradual anticholinergic dose reduction, intermittent anticholinergic prescription and other ways were suggested to avert risk of abuse.